FENOMENA TIDUR BERSAMA BOS : POTRET DOMINASI PRIA DI TEMPAT KERJA - SITI MARIYAM; ADHI PUTRA SATRIA (Universitas Mahasaraswati K. Mataram, 2023)
This is a conceptual article discussing the phenomenon of staycations, or vacations taken in the same location as one's workplace, between bosses and female employees that has gone viral on social media. This practice can potentially lead to sexual harassment of female employees and reaffirms the domination of men over women in the workplace. Furthermore, many staycation victims are reluctant to report incidents due to a lack of trust in the state's protection system for its citizens. In this article, the author will discuss factors that contribute to victims' reluctance to report such harassment, such as gender inequality and power imbalances in work relationships. As a solution, an active role is needed from the government and companies to ensure the safety and protection of employee rights, especially for women. In addition, there is a need for increased awareness and education about workers' rights and self-protection against sexual harassment in the workplace.